No Difference in the Effects of Consuming Commercially Relevant Palmitic Acid- and Stearic Acid-Rich Interesterified Fats on the Plasma Total Cholesterol to High-Density Lipoprotein Cholesterol Ratio: The INTER-SAT Study - Wendy L. Hall; Eleanor Wood; Peter J. Joris; Johanna H. Bruce; Ronald P. Mensink; Sarah E. Berry (Proceedings)
Background and Objectives. Randomly interesterified (IE) palmitic acid (16:0)- and stearic acid (18:0)-rich fats are commonly used by the food industry for applications such as spreads and bakery products. Previous studies demonstrate that 18:0-rich fats (unlike 16:0-rich) do not increase the total:HDL cholesterol ratio (TC:HDL), but the comparative effects of commercially relevant IE fats rich in 16:0 or 18:0 are unclear. Hypothesis: An IE 16:0-rich fat will have equivalent effects on the TC:HDL when compared with a functionally matched 18:0-rich fat. Methods. A randomised crossover trial (clinicaltrials.gov NCT04418102; funded by the Malaysian Palm Oil Board) in healthy adults aged 35–65 was conducted. IE fats provided 10% energy intake for 6 weeks per arm with a minimum 4-week washout period. IE fats were formulated into hardstocks that were baked into muffins and blended into spreads. Spreads contained either 54% IE palm stearin/kernel (PSK) hardstock (16:0, 49%; 18:0, 5%) blended with 36% rapeseed oil (final spread: 16:0, 32%; 18:0, 4%), or 54% IE fully hydrogenated rapeseed oil/coconut oil/high oleic sunflower oil/sunflower oil hardstock (16:0, 7%; 18:0, 41%) blended with 36% rapeseed oil (final spread: 16:0, 6%; 18:0, 25%). The study was conducted at King’s College London and Maastricht University. Results: A total of 51 eligible volunteers were randomised to the treatment sequence; 47 participants completed the study (24 females/23 males; mean age 52 years, SD 8; mean BMI 25.6, SD 3.0). The TC:HDL did not change following FHS (0.03, 95% CI −0.06, 0.12) or PSK (−0.03, 95% CI −0.11, 0.06) and changes did not differ between groups (0.05, 95% CI −0.08, 0.18). The total, HDL and LDL cholesterol and triglyceride concentrations did not change following PSK or FHS and there were no differences in changes between groups. Discussion: Consuming foods made with commercially relevant IE fat blends rich in 16:0 at 10% of the energy intake is unlikely to have a detrimental effect on the TC:HDL when compared with IE fat blends rich in 18:0. These results provide much-needed evidence of the cardiometabolic health effects of industrially processed fats relevant to oil and fat manufacturers, the food industry, health authorities and healthcare professionals.